Computational Design of Thioxanthone Derivatives as Potential Antimalarial Agents through Plasmodium falciparum Protein Inhibition - Faris Hermawan; Jumina Jumina; Harno Dwi Pranowo; Eti Nurwening Sholikhah; Muthia Rahayu Iresha (Universitas Gadjah Mada, 2022)
Plasmodium falciparum (P. falciparum) is the most fatal among the other Plasmodium parasites that infect humans with the malaria disease. Currently, the resistance of P. falciparum against some antifolate drugs has become a severe problem. On the other hand, xanthone and thioxanthone derivatives have been reported to have remarkable antimalarial activity. However, molecular docking studies have not evaluated thioxanthone derivative compounds as antimalarial agents. Accordingly, this research investigated the binding pose and inhibition mechanism of several thioxanthone derivatives against P. falciparum proteins DHFR (PDB ID: 1J3K) and DHODH (PDB ID: 1TV5) through molecular docking study. The compound structures were geometrically optimized using Gaussian 09 software and docked to the receptors using AutoDock4 software. The results showed that the free binding energy of thioxanthone derivatives ranged between -6.77 to -7.50 and -8.45 to -9.55 kcal mol–1 against pfDHFR and pfDHODH, respectively, with RMSD values of less than 2 Å. Compound F (4-iodo-3,4-dihydroxy-thioxanthone) gave the most substantial free binding energy against both proteins. Furthermore, the hydrogen bond interaction of compound F was the same as the native ligands of pfDHFR and pfDHODH. These results suggested that compound F has a more robust interaction in pfDHFR and pfDHODH. Thus, it is promising to further evaluate the compound as a candidate for a new antimalarial agent.